2005
DOI: 10.1530/rep.1.00374
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular calcium and protein tyrosine phosphorylation during the release of bovine sperm adhering to the fallopian tube epithelium in vitro

Abstract: In mammals, sperm adhesion to the epithelial cells lining the oviductal isthmus plays a key role in the maintenance of motility and in the selection of superior quality subpopulations. In the bovine species, heparin and other sulfated glycoconjugates powerfully induce the synchronous release of sperm adhering to tubal epithelium in vitro and may represent the signal which triggers release at ovulation in vivo. Sperm detachment may be due either to surface remodeling or to hyperactivation brought about by capac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
2
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 35 publications
6
37
2
2
Order By: Relevance
“…However, in the present study, we observed that AEA has no effects on sperm-oviduct binding and sperm release, even at a concentration of 5 mM. These data are in agreement with several evidences showing that release of spermatozoa bound to the oviductal reservoir is promoted by capacitation (Lefebvre & Suarez 1996, Gualtieri et al 2005, Talevi et al 2007, Talevi & Gualtieri 2010, whereas AEA has been shown to depress this process, at least in human and boar (Rossato et al 2005, Maccarrone et al 2005. Herein, sperm-ZP binding experiments demonstrated that AEA depresses sperm capacitation also in the bovine species.…”
Section: Sperm-oviduct Interactionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, in the present study, we observed that AEA has no effects on sperm-oviduct binding and sperm release, even at a concentration of 5 mM. These data are in agreement with several evidences showing that release of spermatozoa bound to the oviductal reservoir is promoted by capacitation (Lefebvre & Suarez 1996, Gualtieri et al 2005, Talevi et al 2007, Talevi & Gualtieri 2010, whereas AEA has been shown to depress this process, at least in human and boar (Rossato et al 2005, Maccarrone et al 2005. Herein, sperm-ZP binding experiments demonstrated that AEA depresses sperm capacitation also in the bovine species.…”
Section: Sperm-oviduct Interactionsupporting
confidence: 93%
“…Several studies showed that sperm adhesion to the oviductal epithelium prevents capacitation and depresses the motility (reviewed in Hunter (2008)). However, at the time of release, adhering spermatozoa undergo rapid metabolic changes such as increase in intracellular Ca 2C , protein tyrosine phosphorylation, and flagellar beat frequency, which allow their migration toward the ampullary region (Gualtieri et al 2005). The sperm ascension through the oviduct may involve intermittent phases of adhesions and releases (Smith & Yanagimachi 1990, Demott & Suarez 1992, Nakanishi et al 2004.…”
Section: Introductionmentioning
confidence: 99%
“…There is also evidence from in vitro studies that sulphated glycoconjugates such as heparin can act on oviduct tissues to release sperm from binding (Talevi and Gualtieri, 2001;Gualtieri and Talevi, 2003;Gualtieri et al, 2005). However, very much in line with the overall theme of this essay, the concentrations of heparin or heparin-like glycoconjugates in oviduct luminal fluid are under cyclic ovarian control, reaching a peak during the period of oestrus (Parrish et al, 1989), so one returns to the perspective of gonadal coordination of pre-fertilisation events.…”
Section: Catecholamine and Ca 2þ Ionmentioning
confidence: 77%
“…Moreover, it has been reported that addition of postovulatory isthmic oviductal fluid significantly increases bicarbonateinduced capacitation of sperm recovered from the oviduct (40). This changing interaction between spermatozoa and oviductal epithelial cells cannot easily be mimicked in in vitro models even in highly specialized research laboratories (106)(107)(108)(109). Even the obtaining of a sufficient supply of stage-specific oviductal fluid would prove too complex and expensive to be used in routine assessments of sperm capacitation processes.…”
Section: Limitations Of In Vitro Systemsmentioning
confidence: 99%